ZnCu-MOF dissimilar metal photocatalyst, preparation method and application of ZnCu-MOF dissimilar metal photocatalyst in photocatalytic conversion
The ZnCu-MOF isometallic photocatalyst is synthesized by solvent thermal method, and the synergistic effects of zinc and copper are used to solve the problems of low efficiency and poor selectivity of existing catalysts, achieving efficient photocatalytic organic conversion, and the catalyst has good circulation and thermal stability. sex.
Patent Information
- Application Number
- CN202411494409.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-02-18
AI Technical Summary
The existing metal organic framework catalysts have low efficiency and poor selectivity in photocatalytic organic conversion reactions, and have low visible light utilization.
ZnCu-MOF isometallic photocatalyst is synthesized by solvothermal method, and the synergistic effects of zinc and copper are used to improve catalytic activity and selectivity. The method includes thoroughly mixing the zinc salt, copper salt, carboxylic acid ligand and adenine derivative ligand in an autoclave and reacting at a specified temperature, and finally obtaining the ZnCu-MOF catalyst by multiple washings and vacuum drying.
The efficiency and selectivity of the photocatalytic reaction are improved, and benzimidazole and its derivatives are catalyzed, with a conversion rate of up to 90%, a selectivity of up to 95%, and good cycle stability and thermal stability are shown.
Smart Images

Figure CN119463203A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the preparation of an efficient ZnCu-MOF (zinc-copper metal organic framework) heterometallic photocatalyst and its application in the field of photocatalytic organic conversion. Specifically, the present invention relates to the synthesis of ZnCu-MOF catalyst by a solvothermal method and the use of its photocatalytic performance in organic reactions, especially in the degradation of organic pollutants, synthesis reactions and other photocatalytic conversion processes. Through the technology of the present invention, the efficiency and selectivity of photocatalytic reactions can be improved, promoting the development of sustainable chemical reactions. Background Art
[0002] Metal-organic frameworks (MOFs) are a class of highly ordered three-dimensional porous materials composed of metal ions or metal clusters connected to organic ligands through coordination bonds. Due to their excellent specific surface area, adjustable pore structure and good chemical stability, MOFs have been widely used in catalysis, gas storage, separation and sensing.
[0003] In recent years, photocatalytic technology has attracted widespread attention due to its potential in environmental governance and renewable energy conversion. In particular, in the process of photocatalytic organic conversion, the performance of the catalyst directly affects the efficiency and selectivity of the reaction. Traditional photocatalysts are mostly single metals or metal oxides, which have problems such as insufficient catalytic activity, poor stability and poor selectivity. In order to solve these problems, researchers began to explore the design and synthesis of heterometallic MOF catalysts, using the synergistic effect between different metals to improve catalytic performance.
[0004] As a new type of heterometallic MOF, ZnCu-MOF combines the excellent properties of zinc and copper metals and has good light absorption ability and catalytic activity. The zinc metal center has good photocatalytic performance, while the copper metal center can effectively promote electron transfer and improve catalytic selectivity. Therefore, ZnCu-MOF shows higher catalytic efficiency and better selectivity in photocatalytic organic conversion reactions.
[0005] Although some studies have been conducted on the synthesis and application of ZnCu-MOF, the optimization of preparation and its application in specific photocatalytic reactions still need to be explored in depth. The present invention aims to provide a highly efficient preparation of ZnCu-MOF heterometallic photocatalyst and explore its innovative application in the field of photocatalytic organic conversion to promote technological progress and application development in this field. Summary of the invention
[0006] The purpose of the present invention is to solve the problems of low photocatalytic organic conversion efficiency and low visible light utilization rate of existing metal organic framework materials, and to provide a method for preparing an efficient ZnCu-MOF heterometallic photocatalyst, which has excellent photocatalytic performance.
[0007] A technical object of the present invention is to provide a ZnCu-MOF heterometallic photocatalyst, wherein the catalyst comprises peaks at characteristic positions with strong 2θ angles at 6.5°, 9.31°, 11.42°, 13.26°, 14.8°, 17.6°, 18.8°, 20.0°, and 24.12°; More preferably, peaks at characteristic positions of 2θ angles are formed at 16.3°, 21.12°, 22.22°, 27.73°, 28.5°, and 29.4°.
[0008] In order to identify the product of this case, the present invention further conducted infrared detection, and the catalyst was included in 1494 cm -1 、1585cm -1 、1651 cm -1 、1673 cm -1 、3085 cm -1 The peak appears at the characteristic position.
[0009] Another technical purpose of the present invention is to provide a method for preparing an efficient ZnCu-MOF heterometallic photocatalyst, and the method for preparing the ZnCu-MOF heterometallic photocatalyst mainly comprises the following steps: (1) Weigh an appropriate amount of zinc salt and copper salt and place them in a polytetrafluoroethylene-lined autoclave to ensure that the two are fully mixed. Subsequently, add a certain amount of carboxylic acid ligand and adenine derivative ligand to the reaction system. Thoroughly mix and shake until the solution reaches a uniform state, then add an appropriate amount of acid solution and immediately seal the reactor. Place the sealed reactor in an oven, heat the temperature to the specified reaction temperature, and maintain it for a period of time to ensure that the reaction is fully carried out. After the reaction is completed, the obtained solid product needs to be washed and filtered multiple times in different solvents to remove impurities. Subsequently, the washed solid product is placed in a vacuum drying oven at a set temperature and dried for several hours to obtain the final target product.
[0010] The zinc salt in step (1) is ZnSO4, ZnCl2, Zn(NO3)2, Zn(OAc)2, Zn3(PO4)2; the copper salt is CuSO4, Cu(CH3COO)2, CuCl2, Cu(NO3)2; The zinc salt is preferably Zn(NO3)2, and the copper salt is preferably Cu(NO3)2.
[0011] The molar ratio of zinc salt to copper salt added in step (1) is 1-3:1-3, preferably 2:1.
[0012] In the step (1), the molar ratio of the carboxylic acid ligand to the adenine ligand is 1-3:1-5, preferably 1:2.
[0013] The carboxylic acid ligand is selected from 3,3',5,5'-biphenyltetracarboxylic acid, 3, 3', 4, 4'-biphenyltetracarboxylic acid, [1,1'-biphenyl]-2, 2', 5, 5'-tetracarboxylic acid or [1, 1':3', 1''-terphenyl]-3,3'',5,5''-tetracarboxylic acid, preferably 3,3',5,5'-biphenyltetracarboxylic acid.
[0014] In the step (1), the organic solvent is DMF / H2O, and the volume ratio of the two solvents is 1-3:1-2, preferably 2:1.
[0015] The acid solution is nitric acid, hydrochloric acid, sulfuric acid, or acetic acid, preferably nitric acid. To enhance the coordination ability of the ligand, the pH value of the acid is adjusted to about 1-2.
[0016] In the step (1), the temperature is heated to a specified reaction temperature of 80-140°C and maintained for 3-4 days, preferably the reaction temperature is 100°C and the reaction time is 3 days; In the step (1), after the reaction is completed, the temperature drop gradient of the programmed cooling is 5-20°C / h, preferably 5°C / h.
[0017] In the step (1), the product obtained is subjected to solvent washing 3-5 times, preferably 3 times.
[0018] The product in step (1) is placed in a vacuum drying oven and dried at a temperature of 60-120°C, preferably 80°C, for not less than 12 h.
[0019] Another object of the present invention is to provide a catalyst for the reaction of aniline and aromatic aldehyde, wherein the catalyst is the ZnCu-MOF heterometallic photocatalyst, or the ZnCu-MOF heterometallic photocatalyst prepared by the preparation method; the aniline may also be an aniline derivative, and the aromatic aldehyde may also be an aromatic aldehyde derivative.
[0020] The aniline derivatives include o-phenylenediamine, o-aminothiophenol and o-aminophenol; the aromatic aldehyde derivatives include benzaldehyde and 2-naphthaldehyde.
[0021] A method for catalyzing aniline and aromatic aldehyde using a ZnCu-MOF heterometallic photocatalyst, characterized in that it comprises the following steps: First, weigh a certain amount of aniline derivatives, heteroaromatic aldehyde derivatives and photocatalysts, measure a certain volume of reaction solvent, and put it into a light-transmitting glass bottle. Dissolve fully to ensure uniform dispersion. Then, pass a certain volume of gas to keep the reaction conditions stable. Place the glass bottle under a light source and continue to stir the suspension to promote the reaction. At a certain temperature, irradiate for a certain time to carry out a catalytic reaction. The specific time depends on the experimental design. After the experiment, treat the reaction system, collect the products and analyze them to confirm the success of the reaction and the catalytic effect of the photocatalyst. The reaction formula is as follows:
[0022] R1 is H, alkyl, alkoxy, or halogen; R2 is H, alkyl, alkoxy, or halogen; The alkyl group is a C1-C10 straight-chain alkyl group or a branched alkane; the alkoxy group includes any one of methoxy, ethoxy, and propoxy; and the halogen group includes any one of Cl, F, and Br.
[0023] The molar ratio of the aniline derivative to the heteroaromatic aldehyde derivative is 1-2:1-3, preferably 1:1; The amount of the catalyst relative to the raw material is 6%-10%, preferably 8%. The solvent is methanol, ethanol, acetonitrile, ethyl acetate, dichloromethane, preferably methanol; The gas introduced is air or oxygen. When conditions permit, oxygen is introduced.
[0024] The light source is ultraviolet light, blue light, white light, orange light, green light, preferably blue light.
[0025] The reaction temperature is 3-24 h at room temperature, preferably 6 h.
[0026] The structural stability of the ZnCu-MOF heterometallic photocatalyst described in the present invention after cyclic use in photocatalytic reactions: In the above catalytic reaction process, a recycling experiment of ZnCu-MOF photocatalyst was carried out. ZnCu-MOF can be quickly recovered from the reaction system by centrifugation, washed with a solution, and then used in the next cycle without additional treatment or activation. Repeat the experimental steps of photocatalysis to achieve N cycles.
[0027] The solvent used for the washing is methanol, ethanol, acetonitrile, ethyl acetate, dichloromethane, preferably ethanol.
[0028] The above-mentioned process needs to be implemented N times, where N is greater than or equal to 3.
[0029] Patent beneficial effects The preparation of a ZnCu-MOF heterometallic photocatalyst of the present invention and its application in the field of photocatalytic organic conversion have the following beneficial effects: 1. High catalytic reaction activity and selectivity: Benzimidazole and its derivatives were efficiently catalyzed, with a conversion rate of up to 90%. Low by-product generation, selectivity of up to 95%, the catalyst showed excellent photocatalytic performance.
[0030] 2. Good stability: It maintains high catalytic activity and low catalyst loss during multiple cycles, and has good cycle stability.
[0031] 3. Simple preparation and wide application: ZnCu-MOF is synthesized by solvothermal method under mild conditions and can be mass-produced. It has a good substrate universality range for the conversion of benzimidazole and its derivatives. The catalyst has the advantages of simple preparation and wide application. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 Schematic diagram of the coordination environment and porous characteristics of ZnCu-MOF.
[0033] Figure 2 Fourier transform infrared spectra of ZnCu-MOF, 3, 3', 5, 5'-biphenyltetracarboxylic acid and adenine.
[0034] Figure 3 X-ray powder diffraction spectra of the actual synthesized and simulated ZnCu-MOF.
[0035] Figure 4 This is the H NMR spectrum of 2-phenylbenzimidazole.
[0036] Figure 5 This is the H NMR spectrum of 2-phenylbenzothiazole.
[0037] Figure 6 This is the H NMR spectrum of 2-phenylbenzoxazole.
[0038] Figure 7 This is the H NMR spectrum of 2-(naphthalen-1-yl)-1H-benzo[d]imidazole.
[0039] Figure 8 X-ray powder diffraction spectra of ZnCu-MOF before and after cycling.
[0040] Fig. 9 Fourier transform infrared spectra of ZnCu-MOF before and after cycling.
[0041] Fig.10 Schematic diagram of thermogravimetric analysis of ZnCu-MOF before and after cycling. DETAILED DESCRIPTION
[0042] The present invention will be further described below in conjunction with examples, but the present invention is not limited to the following examples.
[0043] Example 1 Synthesis of ZnCu-MOF crystals: First, weigh 1.44 mmol Zn(NO3)2 (0.4371 g) and 0.72 mmol Cu(NO3)2 (0.1776 g) into a 250 mL beaker and mix well. Then, add 0.45 mmol 3,3',5,5'-biphenyltetracarboxylic acid (0.1515 g) and 0.9 mmol adenine (0.1227 g) to the reaction system. Then add a mixed solvent of 108 mL DMF and 54 mL H2O, mix thoroughly and shake until the solution reaches a uniform state. Then, add 1440 μL of concentrated nitric acid, stir the solution until it becomes light blue and clear, and immediately dispense it into the reactor and seal it. Put the reactor in an oven, raise the temperature to 100℃, and keep it warm for 3 d. After the reaction is completed, cool it down to room temperature at 5 ℃ / h to obtain blue crystals, which are then washed and filtered to remove impurities. Subsequently, the washed solid product was placed in a vacuum drying oven at 80° C. for a drying treatment for no less than 12 h to finally prepare ZnCu-MOF crystals.
[0044] Thermal stability test and analysis: Weigh 6.1 mg of ZnCu-MOF crystals accurately and transfer them to a thermogravimetric crucible for testing. The results show that ZnCu-MOF crystals continue to heat up in an air atmosphere. When the temperature is between 150 and 200 °C, the solvent guest molecules contained in the crystal pores gradually lose their contents. When heated to 345.1 °C, the crystal framework begins to collapse and the weight loss rate reaches 20.8%, proving that ZnCu-MOF crystals have good thermal stability.
[0045] Figure 1 The coordination environment and pores of the ZnCu-MOF prepared in Example 1.
[0046] Figure 2 Fourier transform infrared spectra of ZnCu-MOF, 3, 3', 5, 5'-biphenyltetracarboxylic acid, and adenine: the adenine ligand has a wavelength of 3300 cm -1 The sharp peak near 1673 cm is attributed to the stretching vibration of -NH2. -1 The absorption peak near 1603 cm is attributed to the stretching vibration of C=N on the heterocyclic ring. -1 The absorption peak near is attributed to the C=C stretching vibration on the heterocyclic ring. The carboxylic acid ligand has an absorption peak at 3085 cm -1The broad peak near the ligands is due to the -OH stretching vibration caused by hydrogen bonding between the ligands, which overlaps with the CH stretching vibration (3100-3000 cm -1 ). 1700 cm -1 The absorption peak near 1651 cm belongs to the stretching vibration of C=O group. Because it is a strong absorption peak, it is the easiest to identify in the infrared spectrum. -1 The absorption peaks near 1370 cm are mainly due to the group frequency shift caused by the coordination between C=O on the carboxylic acid ligand and the metal, as well as the superposition of the infrared absorption signals of C=N on the adenine ligand. -1 Nearby are the absorption peaks of the aromatic ring in the carboxylic acid ligand and the C=C on the heterocyclic ring of the adenine ligand. The wave number is slightly shifted due to the coordination effect. For polyaniline, 1494 cm -1 The absorption peak at 1585 cm is attributed to C=N stretching vibration, while the absorption peak at 1585 cm -1 The peaks at are related to the C=C stretching vibration. These two peaks are attributed to the deformation of the benzo ring and the quinone ring, indicating that the benzene ring monomer has been successfully polymerized. Figure 3 X-ray powder diffraction spectra of actual synthesized and simulated ZnCu-MOF: The X-ray powder diffraction simulated spectrum of ZnCu-MOF was compared with the X-ray powder diffraction spectrum of synthesized ZnCu-MOF. It was found that the positions of the diffraction peaks of the two were basically overlapped and there were no other impurity peaks, which means that the ZnCu-MOF prepared by this scheme is a pure substance; Example 1-1 Synthesis of ZnCu-MOF crystals: During the cooling process, the temperature was lowered at a gradient of 10 °C / h until the temperature returned to room temperature. The other synthesis methods were the same as those in Example 1, and ZnCu-MOF crystals were finally prepared.
[0047] Example 1-2 Synthesis of ZnCu-MOF crystals: The sealed reactor was placed in an oven, and the temperature was heated to the specified reaction temperature of 100°C through a precise program temperature control system, and kept warm for 4 days to ensure that the reaction was fully carried out. The other synthesis methods were the same as those in Example 1, and ZnCu-MOF crystals were finally prepared.
[0048] Examples 1-3 Synthesis of ZnCu-MOF crystals: The sealed reactor was placed in an oven and heated to a specified reaction temperature of 120° C. by a precise program temperature control system. The other synthesis methods were the same as in Example 1, and ZnCu-MOF crystals were finally prepared.
[0049] Example 2 Synthesis of 2-phenylbenzimidazole:
[0050] 0.26 mmol o-phenylenediamine (28.1 mg) and 0.26 mmol benzaldehyde (27.6 mg) and 8% of the photocatalyst (ZnCu-MOF described in Example 1) relative to the amount of raw materials were weighed into a glass bottle, and 2 mL of MeOH was added. Then, O2 was introduced for a certain period of time, the glass bottle was placed in a blue light reactor, the suspension was stirred at an appropriate speed, and irradiated at room temperature for 6 hours to obtain 2-phenylbenzimidazole.
[0051] Example 2-1 Synthesis of 2-phenylbenzothiazole:
[0052] Weigh 8% of the photocatalyst (ZnCu-MOF described in Example 1) relative to the amount of raw materials, 0.26 mmol of o-aminothiophenol (32.6 mg) and 0.26 mmol of benzaldehyde (27.6 mg) in a glass bottle, measure 2 mL of MeOH and put it in a clean glass bottle. Dissolve it fully to ensure uniform dispersion. Then, introduce oxygen to keep the reaction conditions stable. Place the glass bottle under blue light and continue to stir the suspension to promote the reaction. Irradiate it for 6 h at room temperature to obtain 2-phenylbenzothiazole.
[0053] Example 2-2 Synthesis of 2-phenylbenzoxazole:
[0054] 0.26 mmol of o-aminophenol (28.4 mg) and 0.26 mmol of benzaldehyde (27.6 mg) and 8% of the photocatalyst (ZnCu-MOF described in Example 1) relative to the amount of raw materials were weighed into a glass bottle, and 2 mL of MeOH was added. Then, O2 was introduced, and the glass bottle was placed in a blue light reactor, the suspension was stirred at an appropriate speed, and irradiated at room temperature for 6 h to obtain 2-phenylbenzoxazole.
[0055] Example 2-3 Synthesis of 2-(naphthalen-1-yl)-1H-benzo[d]imidazole:
[0056] Weigh a certain amount of o-phenylenediamine (28.1 mg, 0.26 mmol), 2-naphthaldehyde (40.6 mg, 0.26 mmol) and 8% of the photocatalyst relative to the amount of raw materials, measure 2 mL of MeOH, and put them into a clean glass bottle. Dissolve them fully to ensure uniform dispersion. Then, introduce oxygen to keep the reaction conditions stable. Place the glass bottle under blue light and continue to stir the suspension to promote the reaction. At room temperature, irradiate for 6 h to obtain 2-(naphthalene-1-yl)-1H-benzo[d]imidazole.
[0057] Example 3 Cyclic stability test and analysis: A ZnCu-MOF photocatalyst (ZnCu-MOF described in Example 1) was used, and a recycling experiment of Implementation Case 2 was carried out, and its cyclic stability was investigated. ZnCu-MOF can be quickly recovered from the reaction system by centrifugation, washed with an ethanol solution, and then used in the next cycle without additional treatment or activation. Experiments have shown that after three experiments, the above-mentioned condensation cyclization reaction can still maintain a high photocatalytic activity. The X-ray powder diffraction (PXRD) spectrum, Fourier transform infrared (FT-IR) spectrum and thermogravimetric (TG) diagram of ZnCu-MOF after the recyclability test remain unchanged, indicating that the ZnCu-MOF photocatalyst has a complete structure after organic conversion, has sufficient stability, and can be recycled and reused.
[0058] Figure 4 This is the H NMR spectrum of 2-phenylbenzimidazole: 1 H NMR (400 MHz, DMSO- d 6) δ 12.91 (s,1H), 8.21 – 8.15 (m, 2H), 7.67 (d, J = 7.5 Hz, 1H), 7.60 – 7.45 (m, 4H), 7.27 –7.16 (m, 2H); It can be seen from the figure that o-phenylenediamine and benzaldehyde are condensed and cyclized to successfully synthesize 2-phenylbenzimidazole.
[0059] Figure 5 This is the H NMR spectrum of 2-phenylbenzothiazole: 1 H NMR (500 MHz, DMSO- d 6) δ 8.10 (d, J = 3.8 Hz, 4H), 7.69 – 7.51 (m, 4H), 7.47 (d, J = 1.2 Hz, 1H); It can be seen from the figure that 2-phenylbenzothiazole was successfully synthesized by condensation cyclization of o-aminothiophenol and benzaldehyde.
[0060] Figure 6 This is the H NMR spectrum of 2-phenylbenzoxazole: 1 H NMR (500 MHz, DMSO- d 6) δ 8.27 –8.16 (m, 2H), 7.80 (ddd, J = 11.7, 7.1, 2.2 Hz, 2H), 7.62 (dtd, J = 7.7, 5.8,5.3, 1.8 Hz, 3H), 7.42 (ddd, J = 7.4, 5.6, 1.7 Hz, 2H); It can be seen from the figure that o-aminophenol and benzaldehyde condensation cyclization successfully synthesized 2-phenylbenzoxazole.
[0061] Figure 7 The H NMR spectrum of 2-(naphthalen-1-yl)-1H-benzo[d]imidazole is: 1 H NMR (500 MHz, DMSO- d 6)δ 13.08 (s, 1H), 8.75 (s, 1H), 8.33 (dd, J = 8.5, 1.8 Hz, 1H), 8.07 (dd, J =16.8, 8.9 Hz, 2H), 8.01-7.97 (m, 1H), 7.79-7.51 (m, 4H), 7.24 (s, 2H); It can be seen from the figure that o-phenylenediamine and 2-naphthaldehyde condensation cyclization successfully synthesized 2-(naphthalene-1-yl)-1H-benzo[d]imidazole.
[0062] Figure 8 This is the X-ray powder diffraction spectrum of ZnCu-MOF before and after recycling: Experiments have shown that after three cycles, the X-ray powder diffraction spectrum of ZnCu-MOF remains basically unchanged, indicating that the structure of ZnCu-MOF is complete after organic transformation, has good stability, and can be recycled and reused.
[0063] Fig. 9 This is the Fourier transform infrared spectrum of ZnCu-MOF before and after cycling: Experiments have shown that after three cycles, the structure and chemical composition of ZnCu-MOF have not changed significantly and it still has good stability.
[0064] Fig.10Schematic diagram of thermogravimetric analysis of ZnCu-MOF before and after cycling: Experiments show that after three cycles, the crystal framework of ZnCu-MOF begins to collapse when heated to 325.8°C, and the weight loss rate is 25.2%, which is not much different from before the cycle, and still shows good thermal stability.
[0065] In summary, this scheme provides a highly efficient preparation of ZnCu-MOF heterometallic photocatalyst and its innovative application in the field of photocatalytic organic conversion. The prepared ZnCu-MOF photocatalyst was applied to the organic conversion of o-phenylenediamine and benzaldehyde, catalyzing the production of benzimidazole and its derivatives with a conversion rate of up to 90%. The catalyst exhibited excellent photocatalytic performance, good cycle stability and thermal stability.
[0066] The above contents are only preferred examples of the present invention, but the present invention should not be limited to the contents disclosed in the examples. Therefore, any equivalent or modified contents completed without departing from the spirit disclosed in the present invention shall fall within the scope of protection of the present invention.
Claims
1. A ZnCu-MOF heterometallic photocatalyst, characterized in that: The catalyst has strong 2θ angle peaks at 6.5°, 9.31°, 11.42°, 13.26°, 14.8°, 17.6°, 18.8°, 20.0°, and 24.12°.
2. The ZnCu-MOF heterometallic photocatalyst according to claim 1, characterized in that: The catalyst includes -1 、1585 cm -1 、1651 cm -1 、1673 cm -1 、3085 cm -1 Peak location.
3. The method for preparing the ZnCu-MOF heterometallic photocatalyst according to claim 1 or 2, characterized in that: The steps include: After zinc salt, copper salt, carboxylic acid ligand and adenine are mixed, a mixed solution of DMF and water is added, and after adding an acid solution, a thermal reaction is carried out in a closed environment. After the reaction is completed, the ZnCu-MOF heterometallic photocatalyst is obtained by washing, filtering and drying.
4. The method for preparing the ZnCu-MOF heterometallic photocatalyst according to claim 3, characterized in that: Zinc salts are ZnSO4, ZnCl2, Zn(NO3)2, Zn(OAc)2, Zn3(PO4)2; Copper salts are CuSO4, Cu(CH3COO)2, CuCl2, Cu(NO3)2; The molar ratio of zinc salt to copper salt is 1-3:1-3, preferably 2:
1.
5. The method for preparing the ZnCu-MOF heterometallic photocatalyst according to claim 3, characterized in that: The molar ratio of the carboxylic acid ligand to adenine is 1-3:1-5, preferably 1:2; the carboxylic acid ligand is selected from 3, 3',5, 5'-biphenyltetracarboxylic acid, 3, 3', 4, 4'-biphenyltetracarboxylic acid, [1, 1'-biphenyl]-2, 2', 5, 5'-tetracarboxylic acid or [1, 1', 3', 1''-terphenyl]-3,3'',5,5''-tetracarboxylic acid; the organic solvent is DMF and H2O, and the volume ratio of the two solvents is 1-3:1-2, preferably 2:
1.
6. The method for preparing the ZnCu-MOF heterometallic photocatalyst according to claim 3, characterized in that: The acid solution is any one of nitric acid, hydrochloric acid, sulfuric acid and acetic acid.
7. The method for preparing the ZnCu-MOF heterometallic photocatalyst according to claim 3, characterized in that: The temperature is heated to a specified reaction temperature of 80-140°C and maintained for 3-4 days, preferably the reaction temperature is 100°C; the reaction time is 3 days.
8. A catalyst for the reaction of aniline with aromatic aldehydes, characterized in that: The catalyst is the ZnCu-MOF heterometallic photocatalyst described in claim 1 or 2, or the ZnCu-MOF heterometallic photocatalyst prepared by the preparation method described in any one of claims 3 to 7; the aniline can also be an aniline derivative, and the aromatic aldehyde can also be an aromatic aldehyde derivative.
9. A method for catalyzing aniline and aromatic aldehyde using a ZnCu-MOF heterometallic photocatalyst, characterized in that: The steps include: Aniline or an aniline derivative, an aromatic aldehyde or an aromatic aldehyde derivative is added to a solvent, and then the ZnCu-MOF heterometallic photocatalyst according to claim 1 or 2, or the ZnCu-MOF heterometallic photocatalyst prepared by the preparation method according to any one of claims 3 to 7 is added, and the reaction is carried out under light and air or oxygen is passed through to obtain a catalytic product, and the reaction formula is as follows: , R1 is H, alkyl, alkoxy or halogen; R2 is H, alkyl, alkoxy or halogen.
10. The method for catalyzing aniline and aromatic aldehyde using ZnCu-MOF heterometallic photocatalyst according to claim 9, characterized in that: The solvent includes any one or more of methanol, ethanol, acetonitrile, ethyl acetate, and dichloromethane, preferably methanol.
Citation Information
Cited By
Metal covalent organic framework Cu3-PA-MCOF photocatalyst and application thereof in thioamide derivative synthesis
CN121293527A